2011
DOI: 10.1021/jo2009752
|View full text |Cite
|
Sign up to set email alerts
|

Organocatalytic Asymmetric Conjugate Addition and Cascade Acyl Transfer Reaction of α-Nitroketones

Abstract: Organocatalytic asymmetric conjugate addition of α-nitroketones to β,γ-unsaturated α-keto esters has been developed. A pyrrolidine-based thiourea-tertiary amine was identified as the best catalyst. The reaction was found to proceed via cascade conjugate addition and acyl transfer reaction. A number of α-nitroketones and β,γ-unsaturated α-keto esters were examined in this transformation. 5-Nitro-2-acyloxypent-2-enoates were obtained in good yields (up to 99%) and enantioselectivities (up to 99% ee). The product… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(15 citation statements)
references
References 43 publications
0
14
0
Order By: Relevance
“…Yan showed that simple bifunctional tertiary aminethiourea catalyst cat1, derived from cyclohexane diamine, provided the expected acyl-protected enoates 3 with moderate to excellent enantiocontrol (62-97% ee, Scheme 4a). 8 The scope of the transformation is large with a limitation encountered using -substituted -nitroketones (R 1 = alkyl), resulting in moderate diastereocontrol (around 2:1 dr). It is of great importance to point out that the two diastereomers are formed with different enantioselectivity.…”
Section: Bifunctional Catalysismentioning
confidence: 99%
See 1 more Smart Citation
“…Yan showed that simple bifunctional tertiary aminethiourea catalyst cat1, derived from cyclohexane diamine, provided the expected acyl-protected enoates 3 with moderate to excellent enantiocontrol (62-97% ee, Scheme 4a). 8 The scope of the transformation is large with a limitation encountered using -substituted -nitroketones (R 1 = alkyl), resulting in moderate diastereocontrol (around 2:1 dr). It is of great importance to point out that the two diastereomers are formed with different enantioselectivity.…”
Section: Bifunctional Catalysismentioning
confidence: 99%
“…The acyl transfer constitutes a driving force for the reaction since it was previously shown that under the same conditions addition of -nitroketones to ,-unsaturated aldehydes with-out the phenol substituent did not induce the corresponding Michael addition. 8 Reduction of the obtained adduct provided an interesting entry into 4-substituted chromane derivatives.…”
Section: Scheme 17 Amino-catalyzed Addition Of -Diketones To Ortho-qmentioning
confidence: 99%
“…When the α-nitro ketone is an acyclic derivative ( 207 ), the dihydropyran 208 becomes unstable and is directly opened to enantioenriched 5-nitropentenoate through a retro-Henry reaction (Scheme ). The best organocatalysts were XXXIV and XXXVI , which allowed the final valuable synthons 210 to be obtained with up to 99% yields with excellent enantioselectivities (in many examples, ee > 99%).…”
Section: Enantioselective Acceptor/donor [4 + 2] Cyclization To 34-di...mentioning
confidence: 99%
“…Also, α-nitroketones have been found to be a popular nucleophilic acyl transfer reagent. In 2011, three research groups namely Wang, Yan and Kwong independently revealed the organocatalytic asymmetric conjugate addition of α-nitroketones to β,γ-unsaturated α-keto esters with the concomitant acyl transfer reaction to the keto group [11][12][13]. Consequently, our group developed an organocatalytic asymmetric Michael-acyl transfer reaction of α-nitroketones with unsaturated pyrazolones, 2-hydroxycinnamaldehydes, γ/δ-hydroxyenones, o-quinone methides, etc.…”
Section: Introductionmentioning
confidence: 99%